Generosity as Capital to Win: Ethnic Minority Chinese and Social Capital in Belu Government Head's Election 2015, East Nusa Tenggara - Mbiri, Adeo; Alfirdaus, Laila Kholid (Jurnal Politik Indonesia: Indonesian Political Science Review, 2021)
This article discusses the modalities of minority ethnic groups to win the 2015 local government head's election in the District of Belu. There were three candidates in the election, two were the local ethnic group residents, and one candidate was Chinese, generally known to be the newcomers (migrants) in Indonesia's social context. Interestingly, the candidate from a minority ethnic group succeeded in winning the election and led the district for the next five years. In addition to the fact that the candidate is from a minority ethnic group, the candidate is not known to be the richest one compared to the others. This article looks at the three candidates' social, political, and economic modalities, applying qualitative research with interviews and observations as the data collection method. Although economic and political modalities are necessary, the results reveal that social modalities remain a key factor in gaining community support. Willybrodus Lay, the local Chinese candidate, paired with Ose Luan, won the election despite not being the wealthiest candidate with the most potent economic modalities. Lay's well-known generosity, and his good relationships with the greater community, and his proximity to various social institutions, especially with churches, mosques, and traditional groups, as well as his personality, led him to win the election. He beat another candidate, known to be the richest among the three, and another one, the most popular in local bureaucracy.